KESIAPAN WAJIB PAJAK DALAM MENGHADAPI PEMERIKSAAN BERDASARKAN PMK NOMOR 15 TAHUN 2025 - Ni Made Puspa Pawitri; Made Andy Pradana Sukarta; Ni Ketut Nadila Suryasari; Ni Wayan Diah Puspita Sari; Made Yessi Puspitha (KRISNA: Kumpulan Riset Akuntansi, 2026)
The self-assessment system requires a supervisory function, one of which is through tax audits to ensure taxpayer compliance. Tax audit procedures have changed with the issuance of Minister of Finance of the Republic of Indonesia Regulation Number 15 of 2025. These changes mark a paradigm shift in tax audits toward faster, more integrated, and digital-based processes. This presents a challenge for taxpayers to adapt their internal systems to prepare for audits. This research is a descriptive qualitative study. Data collection was conducted through interviews, literature review, and triangulation with taxpayers, tax consultants, and tax academics. The results indicate that audit-ready conditions can be achieved if taxpayers can establish good corporate governance and be proactive in ensuring that all tax obligations are properly implemented and documented. Thus, taxpayers can achieve audit-ready conditions, namely readiness to face audits with accurate data and evidence in accordance with tax regulations.